Internal loading potential of phosphorus in reservoirs along a semiarid watershed - Moura,Diana Souza (2020)
ABSTRACT Sediments are important to nutrient dynamics, especially due to phosphorus internal loading. Several studies have observed that internal loading could prevent water quality from improving in lakes, even when external phosphorus loading is significantly decreased. Therefore, there is an urgent need to assess the potential release of phosphorus contained in the sediment, and thus, its potential to impact water quality. In this study, the vertical and horizontal distributions of distinct phosphorus forms in the bottom sediments of artificial reservoirs, located at Forquilha watershed (Ceará, Brazil), were investigated through sequential chemical fractionation. The reservoirs Lagoa Cercada (R#1), Riacho do Algodão (R#2), Riacho Verde (R#3), Cachoeira (R#4), Chagas Manu (R#5), Quandu (R#6) and Balanças (R#7) were investigated. Reservoirs R#1 (most downstream reservoir of the watershed) and R#7 (most upstream reservoir of the watershed) had higher concentrations of total phosphorus (PT) and lower pH values, potentially exerting greater influence in phosphorus concentration in the water column. Reservoirs R#3 and R#4 presented a predominance of residual phosphorus (PRe), the least available fractions of phosphorus and thus, presented a lower potential for internal loading. Reservoirs R#5, R#1 and R#2 showed a tendency of decreasing total phosphorus (PT) as the sediment depth increased, probably indicating an increase of allochthonous phosphorus loading along time. Reservoir R#6 showed the predominance of PFeAl and PCa fractions on points A and B, respectively, showing that the characteristics of the sediments may vary in the same reservoir. Mobile (PM) and iron and aluminum-bound phosphorus (PFeAl) were the least and the most abundant fractions in most of the samples analyzed, respectively.